Biomaterials From Nature for Advanced Devices and Therapies 2016
DOI: 10.1002/9781119126218.ch30
|View full text |Cite
|
Sign up to set email alerts
|

Testing Natural Biomaterials in Animal Models

Abstract: Animal models have been extensively developed in the last decades in biomedical field. Their use has shown particular relevance in fields such as cell biology, genetics, anatomy and development, biochemistry, infection and immunity, cancer research, drugs and vaccine development, tissue engineering and regenerative medicine.Despite major advances regarding in vitro models aiming to mimic the complexity and cellular interaction existing within tissues [1-3], in vivo testing is essential to safely investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…ECM scaffolds, as dHCM, are envisioned to help and accelerate the remodeling of injured tissues in vivo [ 47 ]. By its subcutaneous implantation in animal models, it is possible to obtain information about the elicited inflammatory response towards the biomaterial implanted and about its integration with the host tissue [ 48 , 49 ]. In summary, a healthy host response after biomaterial implantation is characterized by an acute proinflammatory phase mainly orchestrated by neutrophils, monocytes and macrophages, followed by an anti-inflammatory phase mediated by the transition from M1 to M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…ECM scaffolds, as dHCM, are envisioned to help and accelerate the remodeling of injured tissues in vivo [ 47 ]. By its subcutaneous implantation in animal models, it is possible to obtain information about the elicited inflammatory response towards the biomaterial implanted and about its integration with the host tissue [ 48 , 49 ]. In summary, a healthy host response after biomaterial implantation is characterized by an acute proinflammatory phase mainly orchestrated by neutrophils, monocytes and macrophages, followed by an anti-inflammatory phase mediated by the transition from M1 to M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the results revealed through these validated procedures that this unique MA-Kefiran hydrogel should be evaluated, in the future, in animal models, a step midway between in vitro studies and human clinical trials [57]. The in vivo assessment of the developed hydrogel on OA animal models is currently being performed.…”
Section: Biocompatibility Of Ma-kefiran Extractsmentioning
confidence: 98%
“…The foreign body response to biomaterials usually occurs at the implant site with prolonged pro-inflammatory activity. Proinflammatory reactions, M1 cell activation, formation of multinucleated foreign body giant cells and granulomatous inflammation eventually interfere with the mechanical properties of the material and lead to material destruction 31,32 characterized adverse chronic reaction. As seen in Fig.…”
Section: Discussionmentioning
confidence: 99%